2017
DOI: 10.1186/s12929-017-0344-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of dengue fever co-infected with leptospirosis among patients admitted for dengue fever – a pilot study

Abstract: BackgroundDengue and leptospirosis infections are currently two major endemics in Malaysia. Owing to the overlapping clinical symptoms between both the diseases, frequent misdiagnosis and confusion of treatment occurs. As a solution, the present work initiated a pilot study to investigate the incidence related to co-infection of leptospirosis among dengue patients. This enables the identification of more parameters to predict the occurrence of co-infection.MethodTwo hundred sixty eight serum specimens collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 27 publications
0
30
0
1
Order By: Relevance
“…Leptospirosis was excluded based on culture and MAT results. However, since both leptospirosis and dengue are endemic in Salvador and both patients had less than 7 days with symptoms, it is possible that they were infected with both pathogens as has been previously demonstrated in other locations [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 96%
“…Leptospirosis was excluded based on culture and MAT results. However, since both leptospirosis and dengue are endemic in Salvador and both patients had less than 7 days with symptoms, it is possible that they were infected with both pathogens as has been previously demonstrated in other locations [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 96%
“…Dengue is highly endemic in Malaysia with a minimum of 100,000 cases and more than 200 mortalities every year [44]. A recent study by Suppiah et al (2017) reported 11/268 (4.1%) dengue cases to be co-infected with leptospirosis [45]. Although leptospirosis is endemic in Malaysia, the lack of clinical awareness and the evaluation of co-infection with dengue is often neglected, hence delays the appropriate management.…”
Section: Discussionmentioning
confidence: 99%
“…Given the laboratory diagnostic challenges and nonspecific presentation of many clinically evident cases, the burden of reported disease is likely underestimated, as supported by other published data. 1,[18][19][20] We recommend enhancement of awareness about leptospirosis and heightened clinical suspicion when evaluating the ill traveler. Laboratories need to have up-to-date diagnostic methods available; molecular detection techniques are key to early diagnosis, which is helpful for the early initiation of treatment that may substantially reduce morbidity and improve outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…13 The list of differential diagnoses for the evaluating clinician to consider is long, encompassing, among others, malaria, arboviral infections, rickettsial diseases, and typhoid fever, 13,17 and misdiagnosis is common. 6,[18][19][20] Early recognition and treatment may be essential to improve patient outcomes 13,21,22 and minimize hospitalization costs.…”
Section: Introductionmentioning
confidence: 99%